Psoriatic Arthritis and Psoriasis Pathology and Clinical Aspects - Adebajo, Adewale; Boehncke, Wolf-Henning.; Gladman, Dafna D.; Mease, Philip J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This useful book addresses the advances in the development of new approaches to assess and treat psoriasis and psoriatic arthritis. The authors$1 (Bcommitment in advancing knowledge in the fields of these diseases has been greatly helped by organisations such as the group for Research and Assessment of Psoriasis and Psoriatic Arthritis (GRAPPA), which have been at the forefront of education and research into these conditions, alongside other interested international and national organisations. Psoriatic Arthritis and Psoriasis -Pathology and Clinical Aspects is a comprehensive and authoritative book written by experts in the field, aimed at generalists and specialists, researchers and clinicians, together with other health care professionals who look after patients with these conditions.s
Section 1. Historical Aspects -- 1. Historical Perspectives on Psoriatic Arthritis -- 2. GRAPPA Historical Perspective -- Section 2. Epidemiological Aspects -- 3. Classification Criteria for Psoriasis and Psoriatic Arthritis -- 4. Epidemiology of Psoriasis and Psoriatic Arthritis -- 5. The Natural History of Psoriatic Arthritis -- Section 3. Pathological and Genetic Aspects -- 6. Immunopathogenesis of Psoriasis Skin and Nail -- 7. Immunopathology of the Psoriatic Arthritis Musculoskeletal Lesions -- 8. Innate and Acquired Cellular Immune Responses in Psoriasis and Psoriatic Arthritis -- 9. Cytokine Pathways in Psoriasis and Psoriatic Arthritis -- 10. Genetics of Psoriasis -- 11. Update on the Genetics of Psoriatic Arthritis -- 12. Animal Models of Psoriasis and PSoriatic Arthritis -- 13. Mechanisms of Bone Remodelling in Psoriatic Arthritis -- Section 4. Clinical Aspects -- 14. Psoriasis -- 15. Scalp Psoriasis: Clinical Features and Assessment -- 16. Nail Psoriasis: Clinical Features and Assessment -- 17. Psoriatic Arthritis -- Section 5. Imaging -- 18. Imaging Tools in Skin and Nail Psoriasis -- 19. Radiographic Assessment of Psoriatic Arthritis (PsA) -- 20. Psoriasis and Psoriatic Arthritis: Ultrasound Applications -- 21. Magnetic Resonance Imaging in Psoriatic Arthritis -- 22. Future Trends in Imaging Modalities for Psoriasis and Psoriatic Arthritis -- Section 6. Laboratory Tests -- 23. Relevant Laboratory Tests and Therapeutic Monitoring in Psoriasis -- 24. Laboratory Tests for Psoriatic Arthritis. Section 7. Management Aspects -- 25. Paradigms of Treatment in PsA -- 26. Topical and Systemic Therapies for Moderate-to-severe Psoriasis.-27. Oral Non-Biologic Therapies and Non-Pharmacological Therapies in PsA -- 28. Biologic Therapy for Psoriasis -- 29. Biologic Therapy of Psoriatic Arthritis.
Keywords: Rheumatology; Geriatrics; Dermatology; Rheumatology; Geriatrics/Gerontology.; Dermatology